Spatial risk assessment of canine rabies transmission via GIS buffer analysis in Bobonaro municipality, Timor-Leste - Cruz, Zito Viegas da; Pereira, Abrão J.; Machado, Filipe de Neri; Adnyana , I Made Dwi Mertha; Jundaeng, Jarupat (PT. Mega Science Indonesia, 2025)
Rabies is a fatal zoonotic disease caused by Lyssavirus of the Rhabdoviridae family. Timor-Leste experienced a rabies outbreak in March 2024, with a 100% fatality rate, primarily affecting dogs as the main reservoir. Bobonaro Municipality has reported an increasing number of confirmed cases, necessitating spatial approaches for effective control strategies. This study aimed to identify confirmed rabies case distribution patterns and predict transmission risk zones via GIS buffer analysis within the Bobonaro Municipality. This study utilized secondary data from 39 confirmed rabies cases from the Bobonaro Municipal Agriculture Service between January and June 2025. The analysis was conducted via the Buffer and Multiple Buffer tools in ArcGIS 10.8 software. The geographic coordinates of confirmed cases were mapped to generate distribution maps with transmission movement predictions on the basis of locations in each administrative post, village, and hamlet. Mapping revealed that the majority of confirmed rabies cases were concentrated in the northeastern Bobonaro Municipality, comprising the Cailaco administrative post with the hamlets of the Meligo village, such as Bereleu, Daulelo, Liabote, and Mude, plus the Maliana administrative post. Buffer analysis with a 2 km radius identified tendencies for animal movement at risk of local rabies transmission that could spread to humans and other animals, including neighboring municipalities sharing land borders with Bobonaro. GIS-based buffer analysis successfully identified high-risk zones for rabies transmission within a 2 km radius of the average confirmed case locations. These findings provide an evidence-based foundation for policymakers to implement effective and specific rabies control strategies tailored to Timor-Leste's resource-limited environment.